2009
DOI: 10.1186/1471-2458-9-132
|View full text |Cite
|
Sign up to set email alerts
|

Trends in thyroid hormone prescribing and consumption in the UK

Abstract: Background: Thyroid hormone replacement is one of the most commonly prescribed and cost effective treatments for a chronic disease. There have been recent changes in community prescribing policies in many areas of the UK that have changed patient access to necessary medications. This study aimed to provide a picture of thyroid hormone usage in the UK and to survey patient opinion about current community prescribing policies for levothyroxine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 9 publications
(9 reference statements)
1
74
0
Order By: Relevance
“…T hyroid hormone is one of the most frequently prescribed therapies in the United States and Europe, and several studies of primary care practices indicate increasing levothyroxine prescriptions over the past few decades (1,2). Further, thyroid hormone therapy is being initiated for milder thyrotropin (TSH) elevation (3) and in some cases without clear clinical rationale in both primary care (4) and endocrinology specialist settings (5).…”
Section: Introductionmentioning
confidence: 99%
“…T hyroid hormone is one of the most frequently prescribed therapies in the United States and Europe, and several studies of primary care practices indicate increasing levothyroxine prescriptions over the past few decades (1,2). Further, thyroid hormone therapy is being initiated for milder thyrotropin (TSH) elevation (3) and in some cases without clear clinical rationale in both primary care (4) and endocrinology specialist settings (5).…”
Section: Introductionmentioning
confidence: 99%
“…More data are available on changes in thyroid hormone prescription. Thus, the annual number of thyroid hormone prescription items dispensed in England more than doubled from 1998 to 2007 (12), and in the Tayside region in Scotland, the prevalence of treated hypothyroidism increased by 63% from 1994 to 2001 (13). In Denmark, the incidence rate of treated hypothyroidism increased by w80% from 1997 to 2008, which may be explained both by more extensive detection and treatment of hypothyroidism and by an increased incidence of hypothyroidism due to the introduction of iodized salt (14).…”
Section: Huntmentioning
confidence: 99%
“…19,20 Indeed, evidence shows that there may be some disadvantages to shorter prescriptions. Shorter prescriptions may (1) increase the costs to the health system through increased GP administrative workload and dispensing fees to pharmacists, 21 (2) increase costs incurred by the patient, 22 (3) have a negative impact on patient satisfaction 23 and (4) have a negative impact on adherence. 24 Whether or not the most commonly used prescription length should be changed was identified as a key area for research in the DH's 2011 roundtable, Making Best Use of Medicines.…”
Section: Guidance and Policy On Repeat Prescription Lengthmentioning
confidence: 99%
“…In a study on patients' perceptions of, and satisfaction with, a 28-day prescribing policy for thyroid hormone, Mitchell et al 23 found widespread dissatisfaction. The most common reasons cited for being dissatisfied were the inconvenience of having to pick up the prescription/ tablets more frequently, as it interferes with the working day.…”
Section: Limitations Of the Evidencementioning
confidence: 99%
See 1 more Smart Citation